A regulamentação jurídica do uso de células-tronco embrionárias humanas para pesquisa e biopolítica - Rocha, Cintia Pavani Motta (Universidade do Vale do Rio dos Sinos, 2013)
The current model of society that interferes directly in the law, leads to reflections about how the power is drawn in relation to human life. For this analysis we sought to develop an approach based on the concepts of biopolitics and biopower in brazilian legal reality. The Direct Action of Unconstitutionality nº. 3510, which put in question the use of human embryonic stem cell research, was chosen to demonstrate how the powers are exercised and legitimized by human action. It will be demonstrate how law arises as a legitimating device of normalizing power. The conflict between what can be considered human life or mere life are discussed throughout this work, which highlights the importance of understanding the being to determine what may or may not be considered as a human being. And furthermore, how these concepts become part of society and directly influencing judicial decisions in the country.
Keywords: Biopolítica; Biopoder; Célula-tronco; Embrião; Vida humana; Biopolitics; Biopower; Stem cell; Embryo; Human life; ACCNPQ::Ciências Sociais Aplicadas::Direito